KETAHANAN PANGAN: SITUASI, PERMASALAHAN, KEBIJAKAN, DAN PEMBERDAYAAN MASYARAKAT - Purwaningsih, Yunastiti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2008)
The problem of food security is availability, distribution, and consumption. The problem of availability is limited and decreasing production capacity; the distributionâs problems are infrastructure, institution, safety link of distributionâs and the variation production capacity between region and season. The problem of consumption is most of energy consumption are grain and rice biased. The policy of food security not only to create the food sufficiency with development economic with rural and agriculture are the basis, but also the sufficiency of food for poor society. In order to create food reserve of society, lumbung desa is important to be improved.